Enhancement of Biogas Production in Two-Phase Anaerobic Fermentation System for Lower-Temperature Applications - Zhang, Hongqiong; Li, Wenzhe; Sun, Yong; Wang, Xiangyou (Journal of Technology Innovations in Renewable Energy, 2014)
For the purpose of enhancing the biogas production and operation stability of system at low temperature, a two-phase anaerobic fermentation facility for rural household energy generation was proposed. In this facility, the quantity of the fermented materials could be balanced by controlling the hydraulic retention time, which based on pH of the acidification tank and the fermentation tank. In addition, a portion of the biogas generated could be used to heat the acidification tank and the fermentation tank. Results shows that the optimal daily production rate of biogas for 1 m3 fermentation liquid was about 1.47 L/L d-1 at a mixing ratio of cow: swine: chicken manure was 3: 1: 0.5. The production rate obtained in this study was more than four times higher than that from traditional single-phase processes (0.35 L/L d-1). About 5.43 m3 biogas can be produced daily per household with an average CH4 content of 76.8%. The two-phase process developed in this work will also reduce environmental pollution and increase energy production efficiencies.